Penataklasanaan Fisioterapi pada Kasus Faciitis Plantaris Dextra dengan Modalitas Ultrasound dan Terapi Latihan di RS Cahya Kawaluyan - Risma Nurmalasari; Abdul Qudus (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Plantar Fasciitis is heel pain caused by inflammation of the muscle membrane of the soles of the feet called the plantaris fascia. The plantar fascia is located on the surface of the sole of the foot, extending from the calcaneus towards the toes. To determine the implementation of Physiotherapy in reducing pain, increasing muscle strength, and increasing the Scope of Joint Movement in cases of Plantar Fasciitis Dextra using Ultrasound (US) modalities and exercise therapy. After 6 treatments using VAS, it showed a decrease in movement pain from T1 with a value of 3.5 to T6 with a value of 1, a decrease in tender pain from T1 with a value of 6 to T6 with a value of 2, while for silent pain T1 to T6 the value was 0. There was an increase in strength. T1 plantar flexion muscle is worth 4 to T6 is 5, T1 is 3 to T6 is 5, T1 eversion muscle is 3 to T6 5, T1 inversion muscle is 3 to T6 is 5. There is an increase in the range of motion of the ankle joint in the sagittal plane T1 : 150-00-200 becomes T6 : 200-00-350, in the rotation plane T1-T6 : 300-00-200.Ultrasound (US) can help reduce pain and reduce muscle tension. Exercise therapy can increase muscle strength, reduce stiffness and increase joint range of motion.